Handball injuries: Epidemiology and injury characterization: Part 2 - Laver, L.; Luig, P.; Achenbach, L.; Myklebust, G.; Karlsson, J. (Handball Sports Medicine, 2018)
Sports epidemiologic analysis does not rely only on demographic factors but rather the sum of factors controlling the presence or absence of injuries. These factors relate to sports-specific aspects which single out one sport from another and possibly contribute to the injury profile in the sport.